2019
DOI: 10.12968/hmed.2019.80.5.252
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric oncology: assessing the needs of older people with cancer

Abstract: A majority of cancer cases now occur among older people, but this group is less likely to receive treatment and outcomes are poorer than in younger people. Age by itself can be a poor predictor of who will benefit from treatment with surgery, chemotherapy or radiotherapy. Comprehensive geriatric assessment is a multidisciplinary, multidomain process that helps to identify frailty, which is associated with increased mortality. Comprehensive geriatric assessment highlights areas that should be optimized before t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…A study carried out in Ibero-America (Spain, Portugal and Spanish-speaking or Portuguesespeaking countries in America) pointed out that the services are not yet adequately prepared to serve the elderly with cancer, mainly due to the lack of resources and geriatric training for health professionals 10 . Comprehensive geriatric assessment 12 becomes increasingly important, as it can contribute to the early identification of elderly people with cancer, promote individual assessment and in its multiple dimensions -considering, among other aspects, comorbidities, functional state, fragility and physiological factors of senescence -to elaborate , in an interdisciplinary way, the best therapeutic care 35 and in a timely manner for the improvement of the quality of life and greater survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study carried out in Ibero-America (Spain, Portugal and Spanish-speaking or Portuguesespeaking countries in America) pointed out that the services are not yet adequately prepared to serve the elderly with cancer, mainly due to the lack of resources and geriatric training for health professionals 10 . Comprehensive geriatric assessment 12 becomes increasingly important, as it can contribute to the early identification of elderly people with cancer, promote individual assessment and in its multiple dimensions -considering, among other aspects, comorbidities, functional state, fragility and physiological factors of senescence -to elaborate , in an interdisciplinary way, the best therapeutic care 35 and in a timely manner for the improvement of the quality of life and greater survival.…”
Section: Discussionmentioning
confidence: 99%
“…Data from the National Household Sample Survey (PNAD) of 2008 showed that the prevalence of cancer in the ages between 60 and 69 years, 70 to 79 and 80 years or more, were 1.93%, 3.11% and 3.57%, respectively 9 . In addition to investments in prevention policies and the necessary assistance to cancer patients 3,10,11 , with the aging of the population there is also a demand for the expansion of training for oncogeriatric care 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Patients with endometrial carcinoma who require treatment with pelvic EBRT have most risk factors that in uence the development of adverse events. Therefore, radiation oncologists will encounter cases with both short-and long-term adverse events, which will adversely affect treatment and patient survival [30,31]. Accordingly, efforts to reduce healthy tissue (or OAR) toxicity are required.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR genetic screening is routinely performed via tumor tissue biopsy. , Detection methods relying on circulating tumor DNA (ctDNA) sampled from biological liquids are also employed and have the major advantage of being less invasive . ctDNA are linear double-stranded nucleic acid fragments usually between 90 and 320 nucleotides (nt) released in the blood circulation by tumor cells during apoptosis or necrosis. These DNA molecules carry genetic information, such as the T790M mutation in EGFR, distinctive of different types of cancer cells. , Clinical research for the detection and quantification of ctDNA molecules mostly involved next-generation sequencing and PCR-based techniques such as droplet digital PCR and amplification refractory mutation system. , Albeit these methods are now widespread, they suffer from several limitations such as high cost and complexity as well as a long turnaround time. In addition, PCR-based techniques, because of their inherent design, require at least 50 nt on both sides of the mutation of interest for primer annealing. , This means that if, on a given ctDNA molecule, the cancer-related mutation is located close to one of the extremities of the linear fragment, it may not be detected, resulting in a false-negative result.…”
Section: Introductionmentioning
confidence: 99%